2012
DOI: 10.1089/tmj.2011.0194
|View full text |Cite
|
Sign up to set email alerts
|

Patient And phaRmacist Telephonic Encounters (PARTE) in an Underserved Rural Patient Population with Asthma: Results of a Pilot Study

Abstract: Objective: To assess the feasibility, acceptability, and preliminary impact of a telepharmacy intervention in an underserved, rural asthma patient population. Subjects and Methods: Patients with asthma were randomized to receive either standard care or telephone consultations from pharmacists regarding asthma self-management over a 3-month period. Qualitative interviews were conducted to identify participants' attitudes/ opinions regarding the intervention. Baseline and follow-up surveys assessed asthma contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
94
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(95 citation statements)
references
References 36 publications
1
94
0
Order By: Relevance
“…7,28-30 31 In remote areas, technology such as internet support groups, telehealth communication, and teaching models on disease states have been effective tools for improving health literacy, medication adherence, patient engagement and patient empowerment, especially for women. 7,12,23 Our study showed use of internet by respondents for preventative care and some future interest in using telehealth solutions for healthcare. For many rural areas, telehealth has been a great bridging opportunity to improve access and patient care.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…7,28-30 31 In remote areas, technology such as internet support groups, telehealth communication, and teaching models on disease states have been effective tools for improving health literacy, medication adherence, patient engagement and patient empowerment, especially for women. 7,12,23 Our study showed use of internet by respondents for preventative care and some future interest in using telehealth solutions for healthcare. For many rural areas, telehealth has been a great bridging opportunity to improve access and patient care.…”
Section: Discussionmentioning
confidence: 66%
“…22 Details about patient-centric issues were gleaned from the participants using a focus group protocol based on the existing literature, to guide the focus group discussions. 4,7,18,23 The focus group sessions were held in a neutral location -either at the University or the hospital conference room. Demographic information was also collected from each participant.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Other investigators evaluated the telephonic patient-pharmacist encounters that provided information on inhaler use technique and selfmanagement to underserved rural asthma patients. 7,8 These studies showed the need to further demonstrate the role and value of telephonic pharmacist-patient interactions in resolving access barriers and improving patient care delivery. 7,8 M-health services like text messaging can promote safe medication use by improving the knowledge of pharmacists and patients, pharmacist-patient interaction, and pharmaceutical care.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 These studies showed the need to further demonstrate the role and value of telephonic pharmacist-patient interactions in resolving access barriers and improving patient care delivery. 7,8 M-health services like text messaging can promote safe medication use by improving the knowledge of pharmacists and patients, pharmacist-patient interaction, and pharmaceutical care. 7 Whether or not the value of m-health services has been proven, a growing segment of the U.S. population is becoming accustomed to certain mhealth services and, perhaps, beginning to expect such services.…”
Section: Introductionmentioning
confidence: 99%